DIPLOMATIC‌ ‌IMMUNITIES‌ ‌FROM‌ ‌THE‌ ‌PERSPECTIVE‌ ‌OF‌ ‌ CRIMINAL,‌ ‌CIVIL,‌ ‌AND‌ ‌ADMINISTRATIVE‌ ‌JURISDICTIONS‌ ‌ OF‌ ‌THE‌ ‌RECEIVING‌ ‌STATE‌ - Nurhartanto, Gregorius Sri (TANJUNGPURA LAW JOURNAL, 2021)
AbstractA diplomatic mission is the representative of the sending state in the receiving state to carry out a sacred mission. For supporting the functions, diplomatic missions and diplomatic agents are given privileges and immunities rights. The privileges and immunities rights are not for individual diplomatic agents, but more importantly for the benefit of the mission as a whole. The consequence of having the privileges and immunities rights is the diplomatic missions and diplomatic agents are excluded from the local jurisdiction of the receiving state in the areas of criminal, civil and administrative law. This consequence creates complexity for the receiving country to follow up on diplomatic officials and their families if there is a violation or abuse of diplomatic immunity and privileges. There are some exceptions in world history where diplomatic officials can be followed up by recipient countries which can set a precedent for diplomatic immunity and privileges.AbstrakMisi diplomatik adalah misi resmi negara pengirim di negara penerima yang mengemban misi suci. Guna menunjang kelancaran tugas misi diplomatik maka misi diplomatik dan pejabat diplomatik diberikan hak-hak kekebalan dan keistimewaan. Hak-hak kekebalan dan keistimewaan itu bukan semata-mata untuk diri pejabat diplomatik maupun anggota keluarganya, tetapi yang lebih penting adalah untuk kepentingan misi secara keseluruhan. Konsekuensi dari dimilikinya hak-hak kekebalan dan keistimewaan tersebut adalah misi diplomatik dan pejabat diplomatik beserta anggota keluarganya dikecualikan dari yurisdiksi lokal negara penerima baik di area hukum pidana, perdata maupun acara. Konsekuensi ini mengakibatkan kompleksitas bagi negara penerima untuk menindak lanjuti pejabat diplomatik beserta keluarganya bila terjadi suatu pelanggaran maupun penyalahgunaan kekebalan dan keistimewaan diplomatik tersebut. Terdapat beberapa pengecualian terjadi di dalam sejarah dunia dimana pejabat diplomatik dapat ditindak lanjuti oleh negara penerima yang dapat menjadi preseden terkait kekebalan dan keistimewaan diplomatik.